2013
DOI: 10.9766/kimst.2013.16.6.841
|View full text |Cite
|
Sign up to set email alerts
|

Design and Implementation of Biosignal Monitoring for Enhancement of Soldier Survivability

Abstract: Recently, personal health monitoring system using intelligent biosensors and equipments has been realized. This system can be adopted for soldier's biosignal monitoring system. In this paper, we propose a soldier biosignal monitoring system using personal biosensors, such as the ECG sensors and accelerometer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A sample of cadets from the first to fourth grades enrolled at the KMA in 2022 was used to achieve this. Then, the leadership competencies of squad and vice squad leaders in the fourth and third years were determined (Lee, Kim & Chae, 2018). A multiple linear regression analysis was conducted, with the leadership factors for squad and vice squad leaders as independent variables and squad organizational satisfaction as the dependent variable, to identify the leadership factors that influence squad organizational satisfaction.…”
Section: Research Subjects and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…A sample of cadets from the first to fourth grades enrolled at the KMA in 2022 was used to achieve this. Then, the leadership competencies of squad and vice squad leaders in the fourth and third years were determined (Lee, Kim & Chae, 2018). A multiple linear regression analysis was conducted, with the leadership factors for squad and vice squad leaders as independent variables and squad organizational satisfaction as the dependent variable, to identify the leadership factors that influence squad organizational satisfaction.…”
Section: Research Subjects and Proceduresmentioning
confidence: 99%
“…Initially, to collect data for data mining, a questionnaire was administered to assess the organizational satisfaction of each squad. For the data mining procedure, a multiple linear regression analysis was conducted to identify leadership factors with statistically significant effects on squad organizational satisfaction (Lee et al, 2018). 3 Using the results obtained from data mining and employing the theory of integer programming, a data-driven squad formation algorithm was developed to enhance squad organizational satisfaction and leadership discipline effectiveness by considering the identified leadership factors of squad leaders.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, in order to minimize the external magnetic field effects for magnetic sensors in the trigger assembly, it was demonstrated that a magnetic shielding of Fe-Cu-Si-Nd-B had a magnetic-shielding effectiveness of 83 % for an external permanent magnet and 19 % for an alternating magnetic field of 180 dBpT at 60 Hz, respectively. Also, the magnetic shielding had proved experimentally that no virtual trigger signal can be generated by an external magnetic field [3]. However, the shape of the magnetic shielding was restricted by the limited space of small arms and the nature of magnetic sensors that can be operated by a particular magnetic field [4].…”
Section: Introductionmentioning
confidence: 99%